Penggunaan NI/NZA Sebagai Katalis Pada Proses Hidrodeoksigenasi Pirolisis Kulit Pinus (Pinus Merkussi Menjadi Bio-Oil - Anna Apryana; Syaiful Bahri; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Dependence on fossil fuels as an energy source brings us to the energy crisis. Therefore, it is necessary to reduce human dependence on non-renewable energy. One of them is to produce bio-oil from biomass are processed through hydrodeoxygenation pyrolysis technology. One type of biomass that can be used as raw material, namely energy sources pine bark which is a waste of the pine trees. This research aims to produce bio-oil from the bark of pine (pine merkussi) as an alternative fuel, studied the effect of the weight ratio of the catalyst Ni / NZA against biomass, studied the effect of impregnated metal Nickel (Ni) in Natural Zeolite deAluminated (NZA) and characterization of physical properties and the chemistry of the bio-oil is produced. Hydrodeoxygenation pyrolysis process is carried out at a temperature of 320 0C, silinap 500 ml, biomass 50 grams with a size of -100 + 200 mesh sieve, catalyst variation Ni / NZA of the biomass of 4%; 6% and 8% by weight and Ni metal impregnation variation of the Natural Zeolite deAluminated (NZA) of 0%; 1%; 2% and 3%. Results of this study produce bio-oil yields the largest on the use of the catalyst Ni / NZA 8% by weight of the metal content of 3% by 70.99%. Characterization of physical properties of bio-oil obtained in the form of density of 0.980 g / ml, 1,590 cSt viscosity, acidity 32.444 mg NaOH / gram sample, a flash point of 40 0C and calorific value of 44.509 MJ / kg. While the characterization of the chemical properties of bio-oil using Gas Chromatography-Mass Spectroscopy (GCMS) in the can several dominant chemical components such as acetic acid as much as 34.47%, 3-furaldehyde as much as 13.01%, 2-propanone as much as 12.46%, a 1.2-Ethanediol as much as 9:49% and 2-butanone as much as 6.26%.Keywords: Bio-Oil, Catalyst Ni/NZA, Hydrodeoxygenation Pyrolysis , Pine Bark